Membangun Lingkungan Belajar Online Yang Kondusif Dalam Proses Pembelajaran Pendidikan Agama Islam - Fitri, Ayu Laila; Abdul Muhid (Al Hikmah: Jurnal Studi Keislaman, 2023)
The learning environment is one of the keys to the success of the learning process and the achievement of learning objectives. A conducive learning environment can increase students ' interest in learning and activeness of learning. However, since the Covid-19 pandemic, the education system has undergone many changes, especially in the implementation process. Learning that was initially offline becomes online. This is certainly a challenge for every teacher. Building the conductivity of the online learning environment with offline is certainly very different, both in terms of obstacles, methods, and efforts that can be done. This research aims to find out how efforts to build the conductivity of the online learning environment in the PAI learning process in order to achieve the maximum PAI learning objectives. The research method used is qualitative with library research method on online learning environment, conducive learning environment, conducive online learning environment, and PAI learning. The research hypothesis suggests that efforts to build a conducive online learning environment in the PAI learning process are by utilizing a fun online platform, building a positive perception of online learning, streamlining the role of the family as a relationship with teachers, and optimizing several existing theories in educational psychology.